1988
DOI: 10.1177/088532828800300102
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Retrieved UHMWPE Hip Joint Cups

Abstract: In this study it is demonstrated that the combined chemical and mechanical influences of the implant situation cause property changes of ultra-high-molecular-weight polyethylene (UHMWPE) hip joint cups. Nearly 250 loosened hip cups, retrieved 3 weeks to 14 years after implantation, were investigated. The clinical long-term behavior of various shaped polyethylene hip sockets are statistically analyzed. The main damage features were defined and described. Density measurements show a density increase with implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Even though UHMWPE oxidation has been described by several groups [3,4,9,12] we originally reported that the oxidize alkane polymers, within 10 to 16 carbon atoms are by far more immunogenic in TLR1/2 stimulation that the non oxidize counterpart [5]. Herein we complement the previous data with further experiments indicating that TLR1/2 engagement induces a pro-inflammatory transcription program mediated by NFkB signaling pathways, inducing the expression of pro-IL-1β and pro-IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…Even though UHMWPE oxidation has been described by several groups [3,4,9,12] we originally reported that the oxidize alkane polymers, within 10 to 16 carbon atoms are by far more immunogenic in TLR1/2 stimulation that the non oxidize counterpart [5]. Herein we complement the previous data with further experiments indicating that TLR1/2 engagement induces a pro-inflammatory transcription program mediated by NFkB signaling pathways, inducing the expression of pro-IL-1β and pro-IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers began to investigate in vivo degradation of polyethylene in the 1980s but were not able to relate the changes they observed with clinical performance [8][9][10]. Researchers began to investigate in vivo degradation of polyethylene in the 1980s but were not able to relate the changes they observed with clinical performance [8][9][10].…”
Section: Perspective Of In Vivo Oxidation In the 1980s To The Presentmentioning
confidence: 99%
“…3,34,38,39 Therefore, the metal-backed cup, which is designed to reduce the stresses in the bone-bone cement the bone cement. 15,16,18,32,47 In the study by Wroblewski et al, 16 the emphasis of a need for secure adhesion between interface, would be ineffective. Furthermore, studies on metal-back cups revealed that preservation of some elasticthe surface of the UHMWPE and PMMA bone cement was stressed for the improvement of prosthesis fixation in the ity lost from hard metal shell liners is necessary for longterm success.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This showed that what is believed to be a weak mechanical property of bone cement is not a cause for the acetabular cup due to unnecessary introductions of stress concentrators. 47 For long-term efficacy of the THR, it is eventual failure in acetabular components but rather from an imperfect interface in the fixed sites. In cemented THR, necessary and perhaps essential that other effective means of fixation be developed.…”
Section: Introductionmentioning
confidence: 99%